(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In thisstudy researcher observed communicative participation of student withdisability in Mainstream classroom. In communicative participation of studentwith disability researcher seen that communicative participation of studentswith hearing impairment and visually impairment and also compared the communicativeparticipation of students with disability (Hearing impaired and visuallyimpaired) with student with non-disability. Incommunicative participation researcher seen communication interaction means Communicativeinitiation and response with teachers and peers and include both verbal andnon-verbal communicative interaction. For this researcher used survey researchdesign and purposive sampling and selected 10 disabled students (five hearingimpaired and five visually impaired) For data collection researcher usedobservation techniques. Through observation table researcher observed(communicative participation of disabled and non disabled students) that howmany times they initiate and response with peer and teacher. For study tocomparison of communicative participation of 10 disabled and 10 none disabledstudents. Researcher selects each pair (1 disabled& 1 non disabled) one daywas fixed as observation schedule. Researcher used non-parametefic Mann WhitneyU test and Analyze the data. For study the comparison of communicativeparticipation of five students with hearing impaired and five students withvisually impaired. Researcher used descriptive analysis and analyze the dataand also comparison of communicative participation of student Hearing Impairedand Visually Impaired with teacher. Researcher used descriptive analysis. Incomparison of communicative participation of student with disability andstudent with non-disability. Researcher found that communicative participationof student with non-disability is better mainstream classroom. In compressionof communicative participation of student with Hearing Impaired and VisuallyImpaired. Researcher found that communicative participation of Hearing Impairedwas better than student with visually impaired in compression of communicativeparticipation with teacher researcher found that communicative participation ofVisually Children was better than communicative participation of HearingImpaired.